C++ for business programming - Molluzzo, John C. (Prentice Hall, 1999)
"This text provides a very student-friendly introduction to C++ programming. Not assuming any programming experience, the text starts with a gentle introduction to standard, non object-oriented C++ to build a strong foundation in basic programming skills. The second part of the book covers all of the essential object-oriented ideas through inheritance and polymorphism."--Jacket.